Effect of Moringa Oleifera Leaves Meal (MOLM) Supplement in Combating Heat Stress in Broiler Chickens Fed Maize Soya Bean Diet (British Journal of Multidisciplinary and Advanced Studies, 2024)
A growth experiment was conducted for 56 days to study productive performance, carcass characteristics and some blood parameters of broiler chicks fed corn-soybean meal diets supplemented with Moringa Oleifera leaves meals (MOLM) under heat stress condition. Three hundred a day old chicks were randomly assigned to five treatments designated as T1, T2, T3, T4 and T5 supplemented with MOLM (0, 5, 7.5, 10 and 12.5%) respectively. The results did not show body weight gain, feed intake and final weight increased with increased inclusion levels of MOLM, so also was the feed conversion ratio. The cumulative feed conversion ratio was better in T2. The levels of MOLM had no significant effect on carcass relative weight, Haemoglobin (HB), white blood cells (WBC), albumin and total plasma protein increased with increasing levels of MOLM. Mortality rates decreased with increasing levels of MOLM. The best result however, was obtained in T2 (5%) inclusion level. It could be concluded that addition of Moringa Oleifera leaves improved broiler performance, physiological parameters and enhanced the ability to resist heat stress conditions of broilers fed corn-soybean meal diet